2005
DOI: 10.1016/j.jhsb.2005.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age and Gender upon Symptoms and Surgical Outcomes in Carpal Tunnel Syndrome

Abstract: There is conflicting evidence regarding the effectiveness of carpal tunnel release in older patients. This is a prospective study which evaluates the impact of age and gender upon symptoms, self-reported disability and surgical outcome in a series of 97 patients with carpal tunnel syndrome. Symptom severity, hand function and patient satisfaction were assessed using the Boston Carpal Tunnel Questionnaire and the Patient Evaluation Measure. A statistical correlation of age and gender with symptoms, hand functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
81
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 23 publications
(55 reference statements)
7
81
1
3
Order By: Relevance
“…2 However, some investigators have reported that older patients can have a less satisfactory outcome after surgery, 3 though this impression is not universally shared. 4,5 To the author's knowledge, no objective explanation has been suggested for these observations. As the symptoms for carpal tunnel syndrome include wrist pain, paresthesia and weakness in grip strengths, a number of medical conditions can produce a similar clinical picture; therefore, as standard practice, our department investigates these patients with neurophysiology before a surgical treatment strategy is considered if conservative treatment is unsatisfactory.…”
mentioning
confidence: 95%
“…2 However, some investigators have reported that older patients can have a less satisfactory outcome after surgery, 3 though this impression is not universally shared. 4,5 To the author's knowledge, no objective explanation has been suggested for these observations. As the symptoms for carpal tunnel syndrome include wrist pain, paresthesia and weakness in grip strengths, a number of medical conditions can produce a similar clinical picture; therefore, as standard practice, our department investigates these patients with neurophysiology before a surgical treatment strategy is considered if conservative treatment is unsatisfactory.…”
mentioning
confidence: 95%
“…But there are a number of factors associated with poor outcome and patient satisfaction following carpal-tunnel decompression. These factors include diabetes, high age, double crush syndrome, and severity of preoperative symptoms [2,[4][5][6][11][12][13]. General factors associated with poor satisfaction are alcohol abuse, poor mental-health status and involvement of a lawyer [3,7].…”
Section: Discussionmentioning
confidence: 99%
“…There are several factors that are known to influence the outcome of the surgery. These factors include age, duration of symptoms, alcohol use, mental-health status, and presence of objective neurological deficit [2,[4][5][6][7][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines suggest initially trialling wrist splints, but surgical decompression is often considered for patients with insufficient symptom relief [1]. There are divided opinions regarding the impact of age on the efficacy of surgical decompression [2,3], but increasing evidence is mounting that older patients may have a less satisfactory outcome, though may still benefit from a release [4,5]. At the time of initial publishing, the article by Povlsen 'High incidence of absent nerve conduction in older patients with bilateral carpal tunnel syndrome' [6] was, to our knowledge, the first to suggest an explanation based on human patient data.…”
Section: Introductionmentioning
confidence: 99%
“…It must be noted that there is certainly still evidence of benefit for surgical decompression in elderly patients with carpal tunnel syndrome [2][3][4][5]. However, the findings that the extent of nerve damage in these patients may be more extensive, as shown by the nerve conduction study findings, suggest that additional caution may be needed in the risk-benefit analysis when considering surgery in these individuals [10].…”
Section: Introductionmentioning
confidence: 99%